Navigating DR-TB Treatment care: a qualitative exploration of barriers and facilitators to retention in care among people with history of early disengagement from drug-resistant tuberculosis treatment in Johannesburg, South Africa - Ndiviwe Mphothulo; Sindisiwe Hlangu; Jennifer Furin; Mosa Moshabela; Marian Loveday (BMC Health Services Research)
Abstract Background Despite advances in drug-resistant tuberculosis (DR-TB) diagnosis, treatment, and service delivery, individuals with DR-TB often face significant socioeconomic and psychosocial challenges due to limited resources. These challenges can hinder retention in care, undermining the progress made in DR-TB management. As a consequence, advances in DR-TB diagnostics and treatment have not resulted in DR-TB programs meeting the 75% treatment success targets set by the World Health Organization (WHO). Methods We interviewed people with DR-TB who had disengaged from care and their family members to identify barriers and facilitators to retention in care as well as possible strategies to address these barriers. We recruited 16 people with DR-TB and 8 family members from five health facilities in Johannesburg, Gauteng Province, South Africa. All DR-TB patients disengaged from DR-TB care for ≥ 45 days. Semi-structured interviews and focus group discussions were used to collect data, which were analysed through thematic content analysis using a multidimensional adherence model. Results The facilitators of retention in care were positive interactions with health care workers (HCWs), nutritional support, transport from local clinics to DR-TB sites, self-motivation, and emotional support from family members. Barriers to optimal retention in care included a limited understanding of DR-TB disease and treatment, transport challenges, side effects of the medication, pill burden, stigma and discrimination experienced at health care facilities other than DR-TB facilities, food insecurity, and financial difficulties, which included loss of income and a lack of transport money and mental health challenges such as fear, anxiety and feeling lonely and unsupported. Conclusion The findings from this study highlight the need for TB treatment programs to collaborate with people being treated for DR-TB and their families to understand facilitators and barriers to retention in care and how these could be addressed to facilitate optimal retention in care.